Conteúdo e qualidade da matéria orgânica em sistemas de uso e manejo do solo no Bioma Pampa. - Farias, Marla de Oliveira (2010)
Conservation tillage systems contribute to maintaining or increasing soil organic matter (MOS). In Pampa Biome studies that evaluate the dynamics of MOS in agroecossystems under different land use systems and soil management were scarce. The aim of this work was to evaluate the effect of different use systems and soil management on the content and quality of MOS in two different soils of southern of RS. Soil samples from a Albaqualf were collected in Embrapa Clima Temperado, Capão do Leão (RS) in a field experiment with four years, the layer from 0,000 to 0,025 m, in the following treatments: PD no tillage and PC conventional tillage [growihg with ryegrass + birdsfoot (winter) and soybean/corn/sorghum crop rotation (summer)] and CN native pasture. In the entire and the macroagregates samples were chemical fractionated and the content and stocks of total organic carbon (COT), total nitrogen (NT) and the contents and stocks of carbon (C) in the humic fractions (fulvic acid AF; humic acid AH and humin HU) were quantified. The chemical and molecular characteristics of HA extracted were determined by elemental composition (CHNO) spectroscopy, FTIR, EPR and UV-fluorescence visible. The agricultural use resulted in a decrease in COT and C humic fractions in the entire soil and macroaggregates. In the macroaggregates were found the largest proportions of HU fraction. There was a relative enrichment of C of AH form. The elemental composition revealed that AH was rich in N and with high resistance to decomposition and that the macroaggregates under PC in AH showed a higher degree of humification. The FTIR analysis showed that the functional groups of AH are similar among different use systems and management. The analysis of EPR and fluorescence indicates a higher degree of decomposition of organic compounds in soil under PC reflecting a higher degree humification of AH, compared to PD. In another place, soil samples were collected from a Paleaudalf in Estância Sá Brito, Alegrete (RS), in an experiment with five years, in the layers from 0.000 to 0.025 m, 0.025 to 0.075 0.075 to 0.125 m depth. The treatments were: FH homogeneous forests of Eucalyptus grandis; SA silvopastoral system consisting of eucalyptus and pasture; CN pasture native. The entire soil samples were subjected to chemical fractionation and quantified the levels and values of COT and NT contents and C stocks in the humic fractions in AF, AH and HU. The FH system presented potential to promote recovery of MOS in areas with process of the arenization. The most part of the MOS is stored in the humic form substances, especially in the form HU reflecting the importance of the interaction of MOS with the mineral matrix to its preservation and stabilization.